Shelf-life da gordura de aves com diferentes níveis de antioxidantes sintéticos - Boyd, Marianne de Alvarenga (2016)
The aims of the present study were to evaluate the stabilization capacity of five levels (50, 101.26, 225, 348.74 and 400 ppm) of two different synthetic antioxidants, pure BHT and a commercial mix of BHA and BHT (BHA+BHT), in poultry fat, as well as the implications of lipidic oxidation on the palatability of commercial food for cats. The estabilized samples plus a control sample (poultry fat without preserver) were placed inside an oven and submitted to 60°C during 10 days. There were collected smaller samples on predetermined periods by the statistic software Design Expert 7 after 48, 76, 144, 212 and 240 hours of heating. Two samples of fat were maintained at room temperature during 6 months. One was not stabilized with any type of antioxidant and the other was stabilized with 200 ppm of BHA+BHT. In order to observe the lipidic oxidative process in the fat, there were used known methods such as Peroxid Value (PV), Total free fatty acid number (FFA), TBARS, Dienes, Oxitest, Gas chromatography (CGS) and High performance liquid chromatography (HPLC). Poultry fat samples were scanned on NIRS in order to obtain calibration curves for fat quality control. TBARS and PV were the methods that showed better interaction among them. In this study, it was verified that 0.22 mM of equivalent MDA and 10 mEq of peroxide are the limit values to assure the quality of poultry fat. Oxitest proved to be a good method to study the synthetic antioxidants. Also, in this study, when it comes about the control sample, each hour in the oven under 60°C is equal to 0.74 days of storage at room temperature. NIRS is an efficient tool to predict the fat quality when using methods like TBARS and Peroxid Value that presented R2 values of 0.9988 and 0.9954, respectively. The ideal doses of BHT and BHA+BHT when aiming to maintain the fat estabilized for at least 100 days stored, were of 200 ppm and 390 ppm, respectively. With this same study, we were able to see that cats can detect the presence of peroxide in their food however when in low concentrations, it does not affect the consumption by these same animals. The animals showed signs of repulse when the food PV was superior to 5 mEq/kg. Due the losses of essential fatty acids during the fat oxidative process and production of toxic products, cats should not be fed with rancid food.